A new disease allele for the p.C30071R mutation in titin causing hereditary myopathy with early respiratory failure() - Pfeffer, Gerald (Pergamon Press, 2014)
Hereditary myopathy with early respiratory failure is an autosomal dominant myopathy caused by mutations in the 119th fibronectin-3 domain of titin. To date all reported patients with the most common mutation in this domain (p.C30071R) appear to share ancestral disease alleles. We undertook this study of two families with the p.C30071R mutation to determine whether they share the same haplotype as previously reported British families or whether the mutation arose as a de novo event. We sequenced the 119th fibronectin-3 domain in these two probands and flanking polymorphisms associated with the British haplotype in hereditary myopathy with early respiratory failure. A family of Indian descent had a haplotype that was not compatible with the British shared haplotype. Cloning of the 119th fibronectin-3 domain in this patient demonstrated polymorphisms rs191484894 and novel noncoding variant c.90225C>T on the same allele as the mutation, which is distinct from previously reported British families. This proves that the p.C30071R mutation itself (rather than the haplotype containing this mutation) causes hereditary myopathy with early respiratory failure and suggests its independent origin in different ethnic groups.